Photocatalytic removal of imidacloprid containing frequently applied insecticide in agriculture industry using Co3O4 modified MoO3 composites - Adam, Mohamed Shaker S.; Sikander, Sumbleen; Qamar, M. Tariq; Iqbal, Shahid; Khalil, Ahmed; Taha, Amel Musa; Abdel-Rahman, Obadah S.; Elkaeed, Eslam B. (Frontiers in Chemistry, 2023)
Water pollution caused by the frequent utilization of pesticides in the agriculture industry is one of the major environmental concerns that require proper attention. In this context, the photocatalytic removal of pesticides from contaminated water in the presence of metallic oxide photocatalysts is quite an approach. In the present study, Orthorhombic MoO3 has been modified with varying amounts of cobalt oxide through wet impregnation for the removal of imidacloprid and imidacloprid-containing commercially available insecticides. The solid-state absorption responses and band gap evaluation of synthesized composites revealed a significant extension of absorption cross-section and absorption edge in the visible region of the light spectrum than pristine MoO3. The indirect band gap energy varied from 2.88 eV (MoO3) to 2.15 eV (10% Co3O4-MoO3). The role of Co3O4 in minimizing the photo-excitons’ recombination in MoO3 was studied using photoluminescence spectroscopy. The orthorhombic shape of MoO3 was confirmed through X-ray diffraction analysis and scanning electron microscopy. Moreover, the presence of distinct absorption edges and diffraction peaks corresponding to Co3O4 and MoO3 in absorption spectra and XRD patterns respectively verified the composite nature of 10% Co3O4-MoO3. The photocatalytic study under natural sunlight irradiation showed higher photocatalytic efficiency of 10% Co3O4-MoO3 composite among all other contestants for the removal of imidacloprid. Furthermore, the photocatalytic removal of commercially applied insecticide i.e., Greeda was also investigated.